(untitled) (MAUSAM, 2025)
IMD was created to act as the nodal agency in the country on weather and climate matters. This article broadly covers the journey of Climate Services becoming a separate branch with direct linkages to sectoral applications and is not an exhaustive documentation. Notionally, weather and climate differ in the former being a time specified information and the latter a statistical description valid for a certain duration of time. Both, however, refer to geophysical phenomena which impact life as individuals and collective societies. Climatic experiences have for ever lived through memories influencing human activities but in modern times physical observations have been recorded systematically and extensively subjected to mathematical and statistical treatment. This allowed societal applications to be done in objective manner. Of particular interest are the climate effects on agriculture, water resources, health, energy production and safety with respect to climate hazards. Climate services pertain to variability of climate over different periods of time including the changes due to anthropogenic effects. This had made applications of climate knowledge very critical. A framework within which these services need to function are also indicated here.